NARRATIVES OF INTERNAL EXILE IN MARY LAVIN'S SHORT STORIES - Arndt, Marie (International Journal of English Studies, 2002)
Paul Tabori's definition of exile and Michael Seidel's discussion of the "exilic mind" are the points of departure for this study of short stories by Mary Lavin. The stories deal with internal exile, meaning marginalisation within the local community or native country, due to that individual will is incompatible with pressure to conform to unwritten rules of society. The narratives of the stories strongly suggest that these characters are subversive according to the dominant ethos of the restrictive Catholic lreland that Lavin writes about. Women who do not fulfil their enforced social role of wife or mother and the restrictions of young widows feature in several stories. But some stories show that internal exile also affects men, Ieaving thern in a social vacuum. The novella "The Becker Wives" will be discussed at Iength as an explicit and striking narrative of internal exile on an individual and a social level.